Evaluasi Program Keagamaan Dalam Membina Akhlak Siswa di SMP PAB 10 Medan Estate - Salsabila Syfa Siregar; Dedi Masri; Ahmad Darlis (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The background of this research is to find out how the process of evaluating religious programs is in order to find out and ensure that these programs achieve their goals and provide benefits. The aim of this research is to analyze religious program evaluation procedures, the aspects evaluated as well as the constraints and obstacles in the evaluation process. This research uses a type of field research, namely using a qualitative approach. Data was collected through interviews, observation and documentation. Data analysis techniques include data reduction, data display, data presentation and drawing conclusions. The techniques for checking the validity of the data used are source triangulation, technical triangulation and time triangulation. The research results show that the evaluation procedures carried out include planning, implementation and analysis of results. Then the aspects that are evaluated are the spiritual aspects. Student attendance, religious understanding and aspects of attitude change. However, this evaluation is not free from obstacles and constraints. The research results show that the evaluation procedures carried out include planning, implementation and analysis of results. Then the aspects that are evaluated are the spiritual aspects. However, this evaluation is not free from obstacles and constraints. The evaluation results show that the religious program at SMP PAB 10 Medan Estate has a positive impact on the formation of student morals. Students who actively participate in religious activities, especially congregational prayers and reciting the Koran, show an increase in discipline, concern for others, and polite behavior.